ANALISIS PENGARUH KEPERCAYAAN, KEAMANAN, HARGA, KUALITAS PELAYANAN, DAN PERSEPSI AKAN RESIKO TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN E-COMMERCE MELALUI SHOPEE (STUDI PADA MAHASISWA UNISMA) - Nursani Nursani; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aim to determine and analyze the influence of trust, security, price, service quality, and perception of risk on purchasing decisions on E-commerce consumers both partially and simultaneously. The population and sample in this study were 85 people who were all students at UNISMA. Data collection through quetionnaires. Data analysis in this study using the help of SPSS version 14 with data testing techniques used in this study include validity test, reliability test, normality test, classic assumption test, normality test, classic assumption test, multiple linier regression analysis, and testing the research hypotesis. The results of the analysis show that security and service quality partially have no significant effect on purchasing decision while trust, price and perceived risk have a significant effect on purchasing decisions. Simultaneously it shosw that trust, security, price, service quality, and perceived risk influnce the purchasing decisions of E-commerce consumers through the Shopee site.Keywords: Trust, security, price, service quality, perception of risk and purchasing decisions.